Insights into the experiences of older workers and change: through the lens of selection, optimization, and compensation. - Unson, Christine; Richardson, Margaret (The Gerontologist, 2013)
Purpose: The study examined the barriers faced, the goals selected, and the optimization and compensation strategies of older workers in relation to career change. Method: Thirty open-ended interviews, 12 in the United States and 18 in New Zealand, were conducted, recorded, transcribed verbatim, and analyzed for themes. Results: Barriers to finding and maintaining work included task difficulty, problems with coworkers and management, lack of self-confidence, health/physical limitations, ageism, and stereotyping. Respondents' most frequently selected goals for a new career were the desire to help others, work satisfaction, and acquisition of learning. Seventy-five percent of respondents in paid employment had earning an income as a goal. Optimization strategies included drawing on past experience, assessing skills, seeking careers/organizations that fitted their values, and a willingness to accept lower pay or unpaid work. Attitudinal strategies included focus and persistence, optimism, and positive attitudes toward change. The compensation strategies reported were on-the-job training; help from coworkers, clients, or customers; friends and family social support; and professional networks. Management practices considered helpful were flexible work schedules, supervisors' patience, and formal recognition of the value of older workers. Conclusion: This qualitative study, using the SOC framework, showed that evaluating one's skills and values, being positive about change, and being part of a supportive work environment were key contributors to adaptive competence. © 2012 © The Author 2012. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: *Aging/px [Psychology]; *Compensation and Redress; *Employment/px [Psychology]; *Goals; *Self Concept; Aged; Aged, 80 and over; Aging; Compensation and Redress; Employment; Encore careers; Female; Goals; Humans; Inservice Training; Interviews as Topic; Male; Middle Aged; Models, Psychological; Motivation; Multivariate Analysis; New Zealand; Qualitative Research; SOC; Self Concept; Social Support; United States; Workplace; aged; aging; article; compensation; dept.pch; employment; female; human; in service training; interview; male; middle aged; motivation; multivariate analysis; peer-reviewed; psychological aspect; psychological model; qualitative research; self concept; social support; very elderly; workplace

Predictors of success for community-driven water quality management—Lessons from three catchments in New Zealand - Tyson, Ben; Unson, Christine; Edgar, Nick (Applied Environmental Education & Communication, 2017)
Three community engagement projects on the South Island of New Zealand are enacting education and communication initiatives to improve the uptake of best management practices on farms regarding nutrient management for improving water quality. Understanding the enablers and barriers to effective community-based catchment management is fundamental to planning, implementing and evaluating these initiatives. This article investigates some key predictors of success or determinants of effective community engagement. Six factors were identified: access to science, training, and information; confidence in regulatory policies; leadership; farm planning and monitoring; trust in the public; and concern for water quality. © 2017 Taylor & Francis Group, LLC.
Keywords: dept.pch

Dementia and Caregiver Stress: An Application of the Reconceptualized Uncertainty in Illness Theory. - Unson, Christine; Flynn, Deborah; Glendon, Mary Ann; Haymes, Elayne; Sancho, Diane (Issues in mental health nursing, 2015)
The Reconceptualized Uncertainty in Illness Theory (RUIT) was used to investigate antecedents to, appraisals of, and ways of coping with stressful caregiving. Four focus groups with caregivers (8 males and 16 females) of relatives with dementia were conducted; 15 cared for their parents and the remainder cared for their spouses. They were recruited from an adult care center and other community settings in a metropolitan area in New England. The discussions were audiotaped and transcribed verbatim. Two researchers independently coded the transcripts. Thematic analysis was structured according to the RUIT. The study is unique in its application to caregivers as opposed to patients and to all of the elements of the RUIT. Caregivers experience uncertainty in similar ways to patients with life-altering illness. Symptom severity--lack of personal boundaries, repetitive and aggressive behaviors, and the need for constant care--was the most frequent source of stress. The appraisals were mostly negative and included feelings of resentment, a lack of support from family members, financial strains, and loss of freedom. Self-improvement and self-care were important aspects of coping. Spirituality and humor were other coping skills that respondents used. Not all respondents said they were coping and some also reported that support from health care providers was not always helpful. Nurses can help improve coping by explaining the factors that contribute to caregiver strain and uncertainty, and by assisting caregivers to anticipate the effects of the caregiving role.
Keywords: *Adaptation, Psychological; *Caregivers/px [Psychology]; *Dementia/px [Psychology]; *Stress, Psychological/pc [Prevention & Control]; *Uncertainty; Adaptation, Psychological; Adult; Aged; Aged, 80 and over; Caregivers; Dementia; Dementia/th [Therapy]; Female; Humans; Male; Middle Aged; Models, Psychological; Narration; Stress, Psychological; Stress, Psychological/et [Etiology]; Uncertainty; adaptive behavior; adult; aged; caregiver; dementia; dept.nur; dept.pch; etiology; female; human; male; mental stress; middle aged; peer-reviewed; prevention and control; psychological model; psychology; uncertainty; verbal communication; very elderly

Predictors of types of caregiver burden - Unson, Christine; Flynn, Deborah; Haymes, Elayne; Sancho, Diane; Glendon, Mary Ann (Social Work in Mental Health, 2016)
This study identified the types of caregiver stress and the caregiver and care management characteristics that are associated with this stress. 169 caregivers were recruited from a variety of community settings that cater to caregivers in a New England metropolitan area. They completed the Zarit Burden Interview (ZBI) and a questionnaire concerning their care recipient and caregiving arrangements. Principal Components Analysis on the ZBI resulted in five factors: personal strain/loss, uncertainty/inadequacy, social strain/embarrassment, anger, and dependency. The average age of the caregiver was 59.95 years (SD = 11.75) and the average age of the CR was 83.44 years (SD = 7.88). Of the 169 caregivers, 82% were women, 61.5% daughters/in-law or wives (12.9%), 34.3% were solo caregivers; 16.8% little or no burden, 39.9% reported mild to moderate burden, 35% moderate to severe burden, and 8.4% had severe burden. Dependency (22.4%) and personal strain/loss (13.7%) had the highest proportions reported as “often” to “nearly always.” The ZBI was predicted by only two caregiver characteristics, indicating that it is not sensitive to the experiences of different types of caregivers. Caregivers experience different types of burden depending on their gender, kinship roles, and levels of involvement in the care of their older relative. Solo caregiver status and age (younger) significantly predicted most if not all 5 burden types. Solo and young caregivers experienced the highest levels of caregiver burden. Social work practice must identify the caregiver’s life stage and other and self-expectations in relation to dependency, personal loss, embarrassment, anger, or uncertainty. © 2016 Taylor & Francis.
Keywords: Caregiver burden; United States; adult; aged; anger; caregiver burden; controlled study; dependency; dept.nur; dept.pch; expectation; female; gender; human; human experiment; interview; male; principal component analysis; questionnaire; recipient; social work practice; strain; uncertainty